53.7k views
4 votes
Almost doneeeeeeeeeeeeeeee

Almost doneeeeeeeeeeeeeeee-example-1

1 Answer

6 votes

We know that According to Algebra of Real Functions :

If f and g are two real functions which are defined under the same domain then (f + g)(x) = f(x) + g(x)

Given : f(x) = 2x - 1 and g(x) = x² - 3x - 2


:\implies (f + g)(x) = f(x) + g(x) = (2x - 1) + (x² - 3x - 2)


:\implies (f + g)(x) = f(x) + g(x) = x² - 3x + 2x - 1 - 2


:\implies (f + g)(x) = f(x) + g(x) = x² - x - 3

User Keith Vinson
by
5.6k points